Assessment of MLA assertiveness training for librarians: students' behavior changes after taking C.E. 669, Assertiveness and Human Relations Skills. - Caputo, J S (1985)
C.E. 669, offered for three years, was MLA's first personal development continuing education course. Participants were asked to respond to a follow-up survey about their current assertive philosophy, awareness, and behavioral repertoire. They were also assessed by the Librarian's Assertiveness Inventory, a tool that indicates patterns of behavioral responses, for which some normative data were available from librarians who had not taken the class. Class participants were found to be more likely to behave assertively and less likely to behave aggressively than librarians who had not taken the class. In nine out of ten situational categories, librarians who had taken the class demonstrated assertive response patterns. They also reported remembering and using more than one third of the behavioral techniques covered in class, with particular use of the nonverbal techniques. A majority saw themselves as more assertive since taking the class, although most believed that others viewed them much the same as they had prior to the class. Positive progress toward reaching specific behavioral goals was also reported.